Optimizing the role of angklung artists as teaching practitioners in extracurricular learning angklung music in elementary schools - Sari, Nidia; Sularso , Sularso (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2024)
The Angklung music extracurricular activities are one of the activities that students at school are interested in. Teaching artists play a role in helping the process of extracurricular angklung music activities so that students gain knowledge of playing angklung music correctly. This research aims to determine the role of angklung artists as teaching practitioners in extracurricular learning of angklung music and to determine efforts to optimize the role of angklung artists as teaching practitioners in extracurricular learning of angklung music at Muhammadiyah Trini Elementary School. The type of research used is qualitative research. The subjects in this research were angklung artists as practitioners teaching extracurricular angklung music at Muhammadiyah Trini Elementary School. The object of this research is extracurricular learning of angklung music at Muhammadiyah Trini Elementary School, which includes the role of angklung artists as teaching practitioners towards student development in extracurricular angklung music, as well as efforts to optimize the role of angklung artists as teaching practitioners. Data collection techniques are carried out through observation, interviews, and documentation. The research results show that the role of angklung artists as practitioners at Muhammadiyah Trini Elementary School motivates students to continue learning and practicing in extracurricular activities. Apart from that, students' abilities and skills in the field of angklung music are increasing with the presence of angklung artists as practitioners in the class. This study contributes to a broader understanding of artist-led music education and highlights the potential of integrating local cultural arts into educational settings to enrich students' musical abilities and cultural appreciation.